2020
DOI: 10.1590/1807-3107bor-2020.vol34.0104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dental caries and socioeconomic status on social capital throughout adolescence: a 6-year follow-up

Abstract: The aim of the study was to investigate the influence of clinical and socioeconomic factors on social capital throughout adolescence. A cohort study was performed in 2012 (T1) with a random sample of 1,134 12-year-old adolescents from Santa Maria, Brazil. Questions on socioeconomic factors (maternal education, household income, household crowding) were answered by the parents. Clinicians evaluated their dental caries (decayed, missing, and filled status of permanent teeth) and gingival bleeding (using the Comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Several psychosocial and materialistic concepts state that low socioeconomic families are exposed to higher health risks, including lack of access to care and worse environmental factors and living conditions [ 41 ]. From the psychosocial perspective, people living in underprivileged communities are more exposed to anxiety and stress, having an impact on the general quality of life, general health outcomes, and oral health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several psychosocial and materialistic concepts state that low socioeconomic families are exposed to higher health risks, including lack of access to care and worse environmental factors and living conditions [ 41 ]. From the psychosocial perspective, people living in underprivileged communities are more exposed to anxiety and stress, having an impact on the general quality of life, general health outcomes, and oral health.…”
Section: Discussionmentioning
confidence: 99%
“…Human relationships within the community are considered social capital, which is beneficial both to the individual as well as to the community [ 42 ]. An individual having high social capital also benefits from better health behaviors and receives more information from better resources, which can enhance their health status [ 41 , 42 ]. It has been shown that in communities with high social capital, people have a higher life expectancy, lower morbidity and mortality, and better health knowledge [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many causes of inequalities are difficult to identify, in part because they change in relation to their social context [22]. Several studies found significant associations between lower socioeconomic status and higher risk of dental caries [23][24][25][26][27][28][29]. Social factors influence variables associated with caries through modifying living conditions of the individual; it is feasible to gain a more accurate understanding of caries distribution through examining such a relationship.…”
Section: Introductionmentioning
confidence: 99%
“…The items used to assess social capital at T1 and T2 are considered reliable proxies of social capital according to the literature [ 5 , 23 ]. Participants were classified as with high social capital (at least one source of social network or trust) or low social capital (absence of any source of network or trust) for analytical purposes as previously suggested [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%